Letter from Carl D. Duncan to Patricia Whiting, October 7, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan opens this letter with appreciation to Whiting for the time she has spent with him and things she has done for him. Follows is a brief description of their shared enjoyment of music. Duncan concludes the letter with a discussion of a future trip to Indiana and he invites Whiting to use his apartment freely while he is away.